Red Rice Bran Extract Intervention Ability to Improve Lipid Profile and Malondialdehyde Levels in Type 2 Diabetes Mellitus Model Rats - Isniati Dwijayanti; Brian Wasita; Ida Nurwati (Amerta Nutrition, 2022)
Background: Diabetes mellitus accompanied by oxidative stress can cause cardiovascular complications. Red rice bran extract contains antioxidants that have the potential to prevent oxidative stress and improve hyperlipidemia in patients with type 2 diabetes mellitus. Objectives: Analyzing the effect of red rice bran extract on lipid profile and malondialdehyde levels in a diabetes mellitus rat model. Methods: Pretest-Posttest Control Group Design. Thirty-five male Wistar Albino rats were divided into 5 groups, namely, negative control, positive control given acarbose as much as 1.8 mg/200gr/day, and 3 treatment groups given red rice bran extract, 165, 330, 660 mg/kg/day for 21 days, respectively. Results: There was a change in lipid profile and MDA levels (p<0.05) after the treatment of bran extract with doses of 165, 330, and 660 mg/kg BW/day. Red rice bran extract at a dose of 660 mg/kg BW/day can be an alternative to acarbose in reducing cholesterol, LDL, and MDA levels, as well as elevating HDL levels in type 2 diabetes mellitus rats. Conclusions: Red rice bran extract can significantly improve lipid profile and malondialdehyde levels in the type 2 diabetes mellitus rat model. Red rice bran extract at a dose of 660 mg/kg BW/day might be used as an alternative to acarbose in improving lipid profiles and MDA levels.